UPAYA OPTIMALISASI EKSPOR BUAH MANGGIS INDONESIA KE TIONGKOK MELALUI ASEAN-CHINA FREE TRADE AREA (ACFTA) TAHUN 2021 - Zaren, Aisyah Salsabillah; Renolafitri, Hendrini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research discusses the efforts to optimize the export of Indonesian mangosteen to China through the ASEAN-China Free Trade Area (ACFTA) scheme. As a strategic horticultural commodity, mangosteen has a high economic value and plays a role in supporting the national economy. ACFTA provides a significant opportunity for Indonesia with the elimination of tariff barriers and the reduction of non-tariff barriers, thereby further opening up market access to China. This is a qualitative study with data collection conducted through library research and internet research. The theory used is the theory of comparative advantage. This research also employs a state level of analysis, an approach in international relations that views the state as the main actor and unit of analysis in understanding global political, economic, and security dynamics. The research findings indicate that optimizing the export of Indonesian mangosteen to China through ACFTA requires synergy among the government, exporter associations, and business actors. The efforts that must be made include improving product quality through certification, providing modern post-harvest facilities, supply chain efficiency, and diversifying processed mangosteen products to meet Chinese consumer preferences. With this strategy, Indonesia can not only strengthen its position in the international market but also increase the horticulture sector's contribution to national economic growth. Keywords: Mangosteen, International Trade, ACFTA, Export, Horticulture, China, Optimization